Pengaruh Penerapan Model Pembelajaran Problem Solving Dan Pembuatan Peta Konsep Pada Perkuliahan Listrik Magnet - Abdul Hamid (JURNAL FISIKA EDUKASI, 2015)
This study aims to determine the effect of the model-based learning problem solving and concept mapping in electricity and magnetism courses on learning outcomes of students. The study involved 38 students of physical education courses on Education and Teacher Training Faculty Syiah Kuala University Banda Aceh, the group consisted of 24 experimental and 14 control groups. Research procedures using a pretest-posttest control group. Preliminary data collected and the results of student learning with structured essay test techniques. To examine the effect of the application of learning models of problem solving and concept mapping on learning outcomes of students used different statistical analysis on the significant level of 5%. The results of t-test analysis showed that the application of learning models of problem solving and concept mapping effect and can improve student learning outcomes (t = 4.40). So the quality and quantity of student learning outcomes better experimental group compared with the control group students' learning outcomes.